Application of Landscape Ecological Security Pattern Model in Space Space of Zhaoqing - Zhang, Hong (International Journal of Public Health and Medical Research, 2024)
Zhaoqing lake is the main area of Zhaoqing city landscape development, is the core area of Zhaoqing city construction, but has the characteristics of ecological sensitive, limited environmental bearing capacity, with the urban construction and rapid expansion, the ecological environment damage, about Zhaoqing lake ecological protection and sustainable development research is very urgent. From the perspective of landscape ecology, using the minimum cumulative resistance model analysis of Zhaoqing lake landscape ecological security pattern, focusing on Zhaoqing north ridge mountain center and lake ecological corridor between water, and through the urban greenway construction of the minimum ecological corridor space protection, to ensure the urban ecological security.